Use of pyraclostrobin on the nitrate assimilation and agronomic traits of the Pérola common bean cultivar - Alves Dabadia, Ana Claudia; Schumacher, Pedro Vitor; Vanessa da Silva, Andreia; Paulino da Costa Netto, Antônio; Silva Cruz, Simério Carlos; Fialho dos Reis, Edésio (Científica, 2017)
Fungicides of the strobilurin chemical group are efficient in controlling pathogens, but can also act on plants to affect their development and increase grain yield. In this context, the aim of the present work was to verify the physiological effect of fungicides and their application time regarding the action of pyraclostrobin in the Pérola common bean cultivar. For this purpose, the experiment was carried out in an incomplete factorial arrangement (3x2x2+1), with four replications, being three seed treatments combined with the application of pyraclostrobin before or after fertilization, plus one application or non-application of another fungicide with pyraclostrobin, and an additional treatment without fungicide application. The following were evaluated: nitrate reductase activity, chlorophyll index, first pod insertion height and plant height, incidence of diseases, number of pods per plant and number of grains per pod, thousand-grain weight and grain yield. The application of pyraclostrobin before cover fertilization resulted in higher nitrate reductase activity with positive effects on the number of grains per pod, grain yield and plant height of the Pérola bean cultivar.